As Sweet as Their Original Utterance The Reception of the Bible in Aggadic Midrashim - Ḳadari, Tamar 1968- (2022)
This article analyzes the reception of the Bible in a group of midrashim called amoraic midrash , or aggadic midrash , which reveal the centrality of Scripture in the world of the rabbis. Each midrash is organized around a particular biblical book and its verses, bringing a collection of interpretations taught by different rabbis in the land of Israel in the first five centuries of the Common Era. These compositions were redacted towards the end of the Amoraic Period and immediately after and are therefore referred to as midrashei amoraim . The title midrashei aggadah reflects their content, with almost no interpretations dealing with halakhic issues . In this article, I explain the unique fashion in which midrashei aggadah function as a mode of biblical interpretation, the creative ways biblical verses were employed by the rabbis, and the conception of the Bible’s unity evidenced in their midrashim. I then present the main role of biblical verses as an organizing principle in two genres of midrashic compositions. I conclude with the question of the link between midrashei amoraim and the world of the synagogue. Do these midrashim teach us about biblical reception and interpretation solely among the intellectual elite or also among the general public?
Keywords: Rabbinics; Talmud; Biblical Interpretation; Midrash